Relative wage variation and industry location - Andrew B. Bernard; Stephen Redding; Peter K. Schott; Helen Simpson (Institute for Fiscal Studies (IFS), 2003)
Relative wages vary considerably across regions of the United Kingdom, with skill-abundant regions exhibiting lower skill premia than skill-scarce regions. This paper shows that the location of economic activity is correlated with the variation in relative wages. U.K. regions with low skill premia produce different sets of manufacturing industries than regions with high skill premia. Relative wages are also linked to subsequent economic development: over time, increases in the employment share of skill-intensive industries are greater in regions with lower initial skill premia. Both results suggest firms adjust production across and within regions in response to relative wage differences.
Keywords: F11; F14; C14; 330; Deindustrialization; Relative Factor Prices; Diversification Cones; Regionale Lohnstruktur; Produktionsstandort; Großbritannien